2022
DOI: 10.1021/acs.langmuir.2c02229
|View full text |Cite
|
Sign up to set email alerts
|

Plant Latex as a Versatile and Sustainable Emulsifier

Abstract: Emulsions are a class of high-surface-energy materials typically stabilized by surfactants, polymers, particles, or a combination of these. There has been considerable effort to develop new emulsifiers by exploiting developments in synthetic chemistry; however, synthetic surface-active species may assist in the stabilization of a specific type of immiscible liquid–liquid systems. That is, one stabilizer does not provide a solution for all interface stabilization problems. Moreover, the synthesis of surface-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In general, a hydrophilic particle (θ < 90°) gives an o/w emulsion, whereas a hydrophobic particle (θ > 90°) produces w/o emulsions. When a mixture of hydrophilic and hydrophobic particles is used, double or multiple emulsions form. , However, the type of double emulsion (w/o/w or o/w/o) can be controlled by choosing the appropriate proportion of hydrophilic and hydrophobic particles in the system. ,, Thus, the use of a mixture of hydrophilic and hydrophobic particles is vital for the design of double emulsions. In the present work, the sequential addition method is employed to effect the formation of double emulsions in single- and two-particle systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, a hydrophilic particle (θ < 90°) gives an o/w emulsion, whereas a hydrophobic particle (θ > 90°) produces w/o emulsions. When a mixture of hydrophilic and hydrophobic particles is used, double or multiple emulsions form. , However, the type of double emulsion (w/o/w or o/w/o) can be controlled by choosing the appropriate proportion of hydrophilic and hydrophobic particles in the system. ,, Thus, the use of a mixture of hydrophilic and hydrophobic particles is vital for the design of double emulsions. In the present work, the sequential addition method is employed to effect the formation of double emulsions in single- and two-particle systems.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 However, the type of double emulsion (w/o/w or o/w/o) can be controlled by choosing the appropriate proportion of hydrophilic and hydrophobic particles in the system. 18,20,28 Thus, the use of a mixture of hydrophilic and hydrophobic particles is vital for the design of double emulsions. In the present work, the sequential addition method is employed to effect the formation of double emulsions in single-and two- particle systems.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This figure indicates the presence of birefringence in all PEO-stabilized emulsions, indicating the presence of the PEO polymer layer at the decane–water interface. A similar birefringence has been observed in the emulsions stabilized by plant latex . It has been reported that the PEO solution under magnetic stirring could degrade PEO chains into shorter chains and facilitate the formation of insoluble aggregates of several microns.…”
Section: Resultsmentioning
confidence: 99%
“…Oil-in-water emulsions find wide applications in cosmetic, paint, pharmaceutics, petroleum, and food industries . Surfactants, particles, and polymers have been studied as emulsifying agents. However, attention in recent times has been given to naturally occurring emulsifiers such as biosurfactants, phospholipids, biopolymers, and colloidal particles. , Water-soluble polymeric emulsifiers have the balance of hydrophilic and hydrophobic components in their structure to adsorb at the oil–water interface, and their eco-friendly character is an added advantage over the synthetic surfactants. , The polymer at interfaces is widely studied with regard to several aspects such as adsorption, interfacial effects, colloidal stability, and interfacial rheology . For instance, cellulose, which is an abundantly available natural polymer, has been used to stabilize oil-in-water emulsions. , Scanning electron microscopy images of the oil drops showed the presence of a cellulose film at the drop surface.…”
Section: Introductionmentioning
confidence: 99%